Increased platelet expression of glycoprotein IIIa following aspirin treatment in aspirin‐resistant but not aspirin‐sensitive subjects. (August 2014) - Floyd, Christopher N.; Goodman, Timothy; Becker, Silke; Chen, Nan; Mustafa, Agnesa; Schofield, Emma; Campbell, James; Ward, Malcolm; Sharma, Pankaj; Ferro, Albert
<x xml:space="preserve">Abstract</x> Aims Aspirin is widely used as an anti‐platelet agent for cardiovascular prophylaxis. Despite aspirin treatment, many patients experience recurrent thrombotic events, and aspirin resistance may contribute to this. We examined the prevalence of aspirin resistance in a healthy population, and investigated whether the platelet proteome differed in aspirin‐resistant subjects. Methods Ninety‐three healthy subjects received aspirin 300 mg daily for 28 days. Before and at the end of treatment, urine was taken to determine 11‐dehydrothromboxane B2, and blood was taken to measure arachidonic acid (AA)‐induced aggregation of platelet‐rich plasma and to interrogate the platelet proteome by mass spectrometric analysis with further confirmation of findings using Western blotting. Results In two of the 93 subjects, neither AA‐induced aggregation nor urinary 11‐dehydrothromboxane B2 was effectively suppressed by aspirin, despite measurable plasma salicylate concentrations, suggesting the presence of true aspirin resistance. Despite no detectable differences in the platelet proteome at baseline, following aspirin a marked increase was seen in platelet glycoprotein IIIa expression in the aspirin‐resistant but not aspirin‐sensitive subjects. An increase in platelet glycoprotein IIIa expression with aspirin resistance was confirmed in a separate cohort of 17 patients with stable coronary artery disease on long term aspirin treatment, four of whom exhibited aspirin resistance. Conclusions In a healthy population, true aspirin resistance is uncommon but exists. Resistance is associated with an increase in platelet glycoprotein IIIa expression in response to aspirin. These data shed new light on the mechanism of aspirin resistance, and provide the potential to identify aspirin‐resistant subjects using a novel biomarker.